PENGATURAN MEKANISME PELIMPAHAN POKOK PERKARA KE PENGADILAN NEGERI DIKAITKAN DENGAN PUTUSAN PRAPERADILAN YANG DITERIMA MENURUT KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Boy Mono Indra; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The judge's verdict accepts pretrial in order to protect the rights ofsuspects and defendants for the unauthorized conduct of investigation. In this casethe pretrial verdict number. 19/ Pid.Pra / 2016 / PBR. However, pursuant toArticle 82 Paragraph (1) Sub-Paragraph (d) of the Criminal Procedure Code ofPublic Prosecutor for its authority to delegate the principal matter to the districtcourt registered in the case number 535 / Pid.B / 2016 / PN.RHL. Pursuant toArticle 137 of the Criminal Procedure Code does not have a principle ofpresumption of innocence for the rights of suspects and defendants faced beforethe court.The purpose of this thesis writing is: First, to know the setting ofdelegation of principal case to the district court is associated with the pretrialdecision accepted according to the Criminal Procedure Code. Secondly, to knowthe ideal setting of the principal issue of the case to the district court is related tothe pretrial ruling received under the Criminal Procedure Code. Thirdly, to knowthe legal consequences of the transfer of principal case to the district court isrelated to the pretrial decision accepted according to the Criminal ProcedureCode.This type of research is normative legal research or can be called alsoresearch doctrinal law. From the research result of the problem, there are threemain points that are concluded. Firstly, the regulation of the main issue of thecase to the District Court is related to the pretrial ruling which is accepted basedon Ius Constitutum Article 137 KUHAP there is no legal certainty of regulatingrules. So that the principle of Presumption of Innocence (presumption ofinnocence) has ignored the rights of suspects / defendants. Secondly, the idealarrangement of the central delegation mechanism to the District Court is relatedto the pretrial ruling received that the pretrial judgment received by the judgethen the trial in the district court can not be continued so that it is clearlymentioned in the legislation in this case the Book Criminal Procedure Code.Thirdly, the consequence of the law of delegating the principal case to the districtcourt is related to the pretrial decision received, namely the case investigated isthe cessation of prosecution, the case is null and void. The authority of the publicprosecutor has ignored justice for the rights of the accused / defendant.Keywords: Setting-Pretrial-Judgment-Principle of Guilty Prediction